Penerapan Kaidah Lā Ḍarara wa Lā Ḍirār dalam Penggunaan Mercon untuk Mengusir Hama Tanaman - M. Kasim; Muh. Isra Syarif; Ashal Mattanra (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out and understand the concept of lā ḍarar wa lā ḍirār rules as the basis of Islamic law and their application in life, especially in repelling plant pests. This research uses a type of qualitative research in the form of a library research study by conducting a study of books, books and several scientific works related to the discussion of this thesis. Researchers also use a normative juridical approach and a philosophical approach. The results of this research show, firstly, that the use of firecrackers as a means of repelling pests has a huge impact, including violating the ulil amri (Leader), causing noise, fires and wasting property. Second, in the positive law for the use of firecrackers, the punishment for criminal offenses related to firecrackers has been determined, including 12 years, 15 years and a maximum sentence. According to Islamic law, perpetrators of criminal acts will be sentenced to ta'zir, such as death, flogging, imprisonment and exile. Thirdly, the application of the principle of lā ḍarar wa lā ḍirār in the use of firecrackers is not recommended in its use because it contradicts the meaning of the rule of not endangering oneself or others and the Islamic religion also strictly prohibits actions that cause danger and anything that has no benefit. Therefore, alternative solutions such as the use of used cans which are safer are proposed in this problem and are considered more environmentally friendly.